Menuju Pendidikan Inovatif Di Era 5.0: Apakah AI Mampu Membentuk Calon Guru Matematika Yang Mandiri dan Kritis? - Dwi Hatria, Jihan; Noperta (Venn: Journal of Sustainable Innovation on Education, Mathematics and Natural Sciences, 2026)
The rapid growth of Artificial Intelligence in Society 5.0 transforms higher education but raises concerns about dependency. Examining its role in fostering learning independence and critical thinking among pre-service mathematics teachers is essential. This study aims to examine the effect of AI usage, specifically ChatGPT, on learning independence and mathematical critical thinking skills of pre-service mathematics teachers at IAIN Kerinci. A mixed methods approach with a sequential explanatory design was employed. Quantitative data were collected from 30 respondents through Likert-scale questionnaires and critical thinking tests, then analyzed using simple linear regression. Qualitative data from interviews and documentation were used to enrich the interpretation of statistical findings. The results indicate that AI usage has a significant positive effect on learning independence (Sig. = 0.046 < 0.05) and mathematical critical thinking skills (Sig. = 0.000 < 0.05). AI supports self-regulated learning by enhancing initiative, responsibility, and self-control, while also strengthening interpretation, analysis, evaluation, and inference in mathematical problem solving. The findings suggest that AI can serve as a pedagogical support tool that promotes reflective and analytical thinking when accompanied by adequate AI literacy. In conclusion, AI has the potential to contribute to the formation of independent and critical pre-service mathematics teachers in the Society 5.0 era when used consciously and responsibly.